Does merit-based aid promote degree attainment? - Lee, Jungmin (KEDI journal of educational policy, 2018)
This study examines whether receiving merit-based aid affects the bachelor’s degree attainment in the fourth, fifth, and sixth year of initial enrollment in the case of Tennessee. Using the fuzzy frontier discontinuity method, I compare graduation rates of students who initially received the state’s merit-based aid to those of students who did not. Results show that receiving merit-based aid increased the probability of earning a bachelor’s degree in the fourth year. However, it did not affect degree attainment in the fifth or sixth year. This paper also discusses possible explanations regarding why merit-based aid may not influence degree attainment.